AGRICULTURAL EDUCATION: INVESTING BASIC AGRI-FOOD EDUCATION AND AGRIPRENEURSHIP KNOWLEDGE TO EARLY AGE STUDENTS - S Sujarwo; Dian Islami Prasetyaningrum; Yusri Fajar; Edlyn Khurotul Aini; Anisa Aprilia; Putri Budi Setyowati; Fitrotul Laili (Agricultural Socio-Economics Journal, 2021)
The disinterest of the young generation in agriculture carries out awareness in providing agricultural education from an early age. Agri-food education and agripreneurship can be solutions to awake the youth’s awareness that the agricultural sector is also a profitable business. Moreover, the positive perception of farmers as a profession also needs to be grown, especially for early age students. This present study was conducted to increase the interest, competence, and entrepreneurial spirit in agriculture through the implementation of agri-food education and agripreneurship. It was a case study, and the participants were 30 students of 5th grader in SD IT Al-Anwar Mojosari. There were three stages involved: 1) Preparation, 2) Implementation of the Program, and 3) Evaluation. For the data collection, a survey was used as an instrument in this study. The results have shown that there were the high enthusiasm and participation of the students during the activities which are indicated the positive effects of the implemented program.